Managing Potential Fraud in Palembang Hospitals’ Health Insurance Implementation: A Qualitative Study in Indonesia - Emilya, Melda; Misnaniarti, Misnaniarti; Syakurah, Rizma Adlia; Pratomo, Hadi (BPJS Kesehatan, 2025)
Fraud poses a major threat to the integrity of Indonesia’s National Health Insurance–Healthy Indonesia Card (JKN-KIS) program, affecting health financing, hospital quality, and institutional reputation. Despite continuous efforts to combat fraud, allegations persist, particularly in hospitals in Palembang. This study aimed to identify potential fraud in hospitals in Palembang and analyze management countermeasures. Using a descriptive qualitative design with a phenomenological approach, the study was conducted from March to July 2022 and involved three hospitals in Palembang, the City Health Office, and the local branch of the Social Security Administrative Body for Health (BPJS Kesehatan). Data were collected through in-depth interviews with 16 informants representing hospitals, BPJS Kesehatan, and anti-fraud teams, supported by observations and document reviews. Thematic analysis revealed several fraud risks, including diagnosis manipulation, unnecessary treatment, and overcharging. Weak internal and external monitoring mechanisms fostered opportunities for fraud, often driven by financial pressure, revenue targets, and personal motives, and influenced by tenure and position within the organization. Fraud countermeasures remain suboptimal, although BPJS Kesehatan’s management shows potential that requires further improvement. Applying the Hexagon Vousina theory, this study emphasizes the need for a more comprehensive and integrated approach to fraud risk management. Strengthening oversight, professional ethics, inter-agency coordination, and policy enforcement is crucial to maintain the sustainability and effectiveness of the JKN-KIS program.